Pembiasaan Shalat Dhuha untuk Mengembangkan Akhlak Anak di Pedesaan (Laporan Pengabdian Masyarakat di Desa Karangpaningal Kabupaten Ciamis) - Iwan, Cecep Darul; Novendi, Kevin; Saatudarini, Mila; Jabbar, Riska Abdul (Khidmat, 2021)
The concept of religious education, which involves the imparting of spiritual and moral values, is currently being subjected to scrutiny. This pertains to the instruction of religious beliefs, particularly Islamic teachings, at schools or madrasas, which, in practice, continues to exhibit numerous unfavourable issues. Consequently, schools should implement a programme or activity that aligns with religion instruction to enhance moral development. In today's day of rapid scientific and technological advancements, the educational process no longer solely relies on traditional face-to-face instruction. Alternatively, this can be achieved through the process of habituation starting from a young age. It is imperative to instill in youngsters the importance of obedience in worship by consistently guiding them to conduct required and sunnah prayers. As a parent, you can only instruct your child to be obedient in worship at home, relying on the teachers to provide guidance when they are at school. This study employs a qualitative descriptive methodology, specifically utilising field research as the chosen approach. The findings of this study indicate that executing the dhuha prayer programme in congregation in Karangpaningal Village can effectively impart moral values and promote a sense of discipline and responsibility. (2) Conducted daily prior to the learning procedure. (3) Engaging in dhuha prayers prior to teaching and learning endeavours is a deliberate endeavour to establish a devout and exceptional basis for children. The aspects that contribute to the cultivation of moral values through the practice of Duha prayers in Karangpaningal Village include the teachers' strong passion, the students' high level of awareness and enthusiasm, as well as the presence of sufficient facilities and infrastructure. However, the obstacles to promoting moral values through the practice of Duha prayers in Karangpaningal Village include insufficient family support, a number of undisciplined students, and restricted water supply.